Complexos heterobilantanídicos luminescentes sob excitação UV e raios X - Cagnin, Flavia [UNESP] (2014)
Monometallic and/or heterobimetallic Ln3+ (Ln = Eu, Gd, Tb, Dy) luminescent complex with thiophen-2-carboxylic acid was investigated. The ligand employed in this work, acts efficiently as antenna, absorbing and transfer energy to the emitter ion. The thiophen ring provides interesting features to the system, like higher polarizability due the sulphur atom. The complex were characterized by elemental analysis, complexometric titrimetry with edta, in order to quantify Ln3+, thermal analysis, FTIR and XRD which allowed propose two different stoichiometries [Ln(α-tpc)3(α-Htpc)2]n and [Ln(α-tpc)3(α-Htpc)] and the coordination of the ligand to the Ln3+ occurs through the bidentate coordination mode. By the UV-vis, photoluminescence and X rays spectroscopies, were observed the Ln3+ transitions. Energy transfer mechanism were proposed in monometallic and heterobimetallic complexes, from the drafting of the energy diagram, based on results of fotoluminescence. The complex also have the magnetic properties investigated, by the EPR, PPMS and VSM techniques and the results shows a predominantly paramagnetic behavior to the complexes. The complexes were exposure to ionizing radiation during a extended time, in order to verify the chemical stability of the homo and hetero-lanthanide complex forward to ionizing radiation and is observed high stability over X-ray excitation.